2012
DOI: 10.1590/s1679-45082012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem cavernomas: a surgical challenge

Abstract: Objective: The authors show their experience with brainstem cavernomas, comparing their data with the ones of a literature review. Methods: From 1998 to 2009, 13 patients harboring brainstem cavernomas underwent surgical resection. All plain films, medical records and images were reviewed in order to sample the most important data regarding epidemiology, clinical picture, radiological findings and surgical outcomes, as well as main complications. Results: The mean age was 42.4 years (ranging from 19 to 70). No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
(50 reference statements)
0
10
0
2
Order By: Relevance
“…The average modified Ranking Score (mRS) had a mean of 2.36 and median of 2 (Table I), and in the last followup assessment, the average mRS score had a mean of 1.84 and median of 1. The mean follow-up period was 4.64 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) years. Compared with their preoperative states, 14 patients (56%) recovered, 7 (28%) remained unchanged, 3 (12%) got worse and 1 (4%) died.…”
Section: █ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average modified Ranking Score (mRS) had a mean of 2.36 and median of 2 (Table I), and in the last followup assessment, the average mRS score had a mean of 1.84 and median of 1. The mean follow-up period was 4.64 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) years. Compared with their preoperative states, 14 patients (56%) recovered, 7 (28%) remained unchanged, 3 (12%) got worse and 1 (4%) died.…”
Section: █ Resultsmentioning
confidence: 99%
“…In a series involving 13 cases, De Aguiar et al reported that the admission complaints were cranial nerve paralysis (7 and 8) in 92% of the patients, hemiparesis in 7% and headache in 7%. Only one patient recovered from cranial nerve paralysis in the postoperative period (2). In a study involving 36 cases by Samii et al, it was reported that 72% of the patients had cranial nerve paralysis, 36% had motor paralysis and 47% had sensory loss (18).…”
Section: Cms Located In the Ponsmentioning
confidence: 97%
“…The most commonly reported cause of death was postoperative cranial nerve palsy with consecutive respiratory failure/pneumonia in 10 patients (24.4%) [7,[10][11][12][22][23][24][25]. In 7 patients (17.1%), the causes of death were not further clarified; however, it was stated that the death was attributable to BSCM surgery [16,19,[26][27][28][29][30]. Both cardiopulmonary arrest and re-bleeding of incomplete resected BSCM led to death in 3 patients (each 7.3%) [5,[31][32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…O exame de imagem padrão-ouro para o diagnóstico de cavernomas é a RM 13 , e isto se deve à sua alta resolução espacial e a uma grande sensibilidade na detecção de produtos de degradação da hemoglobina 1 . O achado clássico em T1 costuma ser uma lesão arredondada com aspecto em "pipoca" 1 , ou seja, de aparência reticulada e com intensidades de sinal mistas 5,13 . Também é característica a presença de halo de hipossinal em T2 devido à deposição de hemossiderina 1 , situação esta que resulta de hemorragias microscópicas 19 .…”
Section: Discussão Radiológicaunclassified